Bahasa Inggris - Muhammad Uwais Al Qorni; Noor Hidayati; Andi Ulfiana (MBI, 2024)
The Priok PLTGU Block 4 Chlorination Plant had experienced component damage, which is the electrolysis generator B, to be precise in the 4th order electrolysis cell. One of these cells was damaged which caused the current and voltage used for the electrolysis process to become unstable and required handling of the incident. The handling step taken by the operator is to switch over to the electrolysis generator A which has a standby status. In this study the authors aim to create simulation conditions, and see the feasibility of performance if the electrolysis generator is still running using only 3 cells. The feasibility of the performance is assessed based on a comparison of the concentration of chlorine produced, then compared with the minimum requirement for the generating unit's water purification system, and calculating the available residual chlorine. The results of this study indicate that the concentration of chlorine resulting from the operation of the 3 cell mode is not much different from the normal 4 cell operation, and is able to meet the min-imum requirement of chlorine for the generator, as well as the residual which is classified as safe limits so that the 3 cell operating mode is classified as feasible to operate.